Benzo[a]pyrene induces intercellular adhesion molecule-1 through a caveolae and aryl hydrocarbon receptor mediated pathway - Oesterling, Elizabeth (2008)
Toxicologic and epidemiologic studies have linked benzo[a]pyrene (B[a]P) exposure with cardiovascular diseases such as atherosclerosis. The mechanisms of action leading to these diseases have not been fully understood. One key step in the development of atherosclerosis is vascular endothelial dysfunction, which is characterized by increased adhesiveness. To determine if B[a]P could lead to increased endothelial adhesiveness, the effects of B[a]P on human endothelial cell intercellular adhesion molecule-1 (ICAM-1) expression was investigated. B[a]P was able to increase ICAM-1 protein only after pretreatment with the aryl hydrocarbon receptor (AhR) agonist β-naphthoflavone (β-NF). Knockdown of AhR by siRNA or treatment with AhR antagonist α-naphthoflavone (α-NF) eliminated the induction of ICAM-1 from B[a]P, confirming the necessity of AhR in this process. Likewise, B[a]P only increased monocyte adhesion to the vascular endothelium when cells were pretreated with β-NF. Experiments were done to define a signaling mechanism. B[a]P increased phosphorylation of MEK and p38-MAPK, and inhibitors to these proteins blunted the ICAM-1 induction. B[a]P was also able to increase AP-1 DNA binding and phosphorylation of c-Jun. Phosphorylation of c-Jun was disrupted by MEK and p38-MAPK inhibitors linking the signaling cascade. Finally, the importance of membrane microdomains, caveolae, was demonstrated by knockdown of the structural protein caveolin-1. Disruption of caveolae eliminated the B[a]P induced ICAM-1 expression. These data suggest a possible pro-inflammatory mechanism of action of B[a]P involving caveolae, leading to increased vascular endothelial adhesiveness, and this inflammation may be a critical step in the development of B[a]P-induced atherosclerosis.